2023
DOI: 10.3126/mef.v13i01.56023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Workplace Stressors on Employee Burnout: A Survey on Diversified Professionals

Abstract: The study has focused on the impact of workplace stressors explained byworkload, work hours, unsupportive supervisors, and unfair treatment on employee burnout. The study adopted a quantitative research approach using a survey method. Professional employees of different sectors have been considered as the population. The 115 usable samples have been taken for the study purpose. The sample has been taken purposively. Five Point Likert Scale and multiple-choice questionnaire have been used for the collection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…One of its possible stressors was the length of working hours. In a study on diversified professionals, it was found that the length of working hours was a major predictor of employee burnout (Pandey & Risal, 2023). In a study by Tamunomiebi & Mezeh (2021), it was found that long working hours of some employees were the cause of the increased rate of ill health.…”
Section: Working Conditions and Workplace Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of its possible stressors was the length of working hours. In a study on diversified professionals, it was found that the length of working hours was a major predictor of employee burnout (Pandey & Risal, 2023). In a study by Tamunomiebi & Mezeh (2021), it was found that long working hours of some employees were the cause of the increased rate of ill health.…”
Section: Working Conditions and Workplace Relationshipsmentioning
confidence: 99%
“…Nevertheless, although seldom, it was still experienced by employees. It was a workplace stressor, that if not checked, would lead to employee burnout (Pandey & Risal, 2023), employee turnover (Borg & Scott-Young, 2022), and even affect organizational productivity (Sangadji et al, 2023). Based on the results, workplace relationships were also seldom experienced.…”
Section: Working Conditions and Workplace Relationshipsmentioning
confidence: 99%